93.4k views
4 votes
SOLVE USING THE QUADRATIC FORMULA

1) y=3x^2-x-6

2) y=-5x^2+7x+3

User Cassidy
by
5.0k points

1 Answer

6 votes

Answer:

Explanation:

Identify the coefficients of the x terms. They are a = -5, b = 7 and c = 3.

The discriminant (the part of the quadratic formula that's under the square root operator) is then b^2 - 4ac, or 7^2 - 4(-5)(3), or 49 + 60, or 109. Because this is positive, we know that 2) y=-5x^2+7x+3 has two real, unequal solutions.

By the quadratic formula, we have:

-7 ± √discriminant

x = ------------------------------ or:

2(-5)

-7 ± √109

x = -------------------

-10

User Keith Entzeroth
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.